Media, Crime and Publik - Bakić-Tomić, Ljubica (Array, 2006)
A b s t r a c t The media of mass communication are not primarily the service of informing the public and that, when reporting on crime, the objectives and the ethics of journalism do not require information released for the purpose of crime prevention. The wider public favours interesting and valuable information about unusual and serious crimes and expects such stories from the press. If we have in mind the fact that reporting on the majority of crimes in a certain area is inadequate, it is clear that the population gets a misleading picture about the crime in their living area. For example, the large national survey in Great Britain (British Crime Survey, 1997) showed that 75% of respondents believe that the crime was on the increase although the actual data showed that the crime rate dropped by 8%. Ever since the mass media have appeared and become popular, the researches in America show that between 10 and 25% of the news report on the safety of the nation (Anderson, Mygler in 1987 ; Surette in 1998 ; Police Operation Poll in 2002). The media influence the reality. For some people the reality as presented by the media is the only reality they know (Splichal in 1994 ; Barak in 1994). The media do not present information in a neutral way. They do not depict the reality as it is, but they submit information and news to the process called gate-keeping as “ the process of media control over the information which involves the selection of the news, their keeping, mediation, shaping, releasing and repeating” as well as “ newsworthiness” which is mentioned by many authors (Shoemaker in 1991 ; Chandler in 1998) as “ news worth releasing” , that is, the aspect of worthiness which the news has for the media as the institution. Those are mainly sensational, surprising, conflicting, controversial, different and peculiar kinds of news which are the criteria that researchers have found in relation to the media presentation of events. The positive influence of the media in the mediation between the police and the public comes with the development of the society. The state has given great powers to the police whose abuse can be controlled by the public only through the media. In addition, the media have a positive social function of determining the limits of acceptable social behaviour (Surette in 1998), the task of informing citizens about the safety situation and taboo subjects (domestic violence, sexual abuse, child/woman abuse, etc.). There should be communication with the public and not only giving information. This conclusion also applies to the media as the mediator.